Women's Agency In Divorce From Stigma To Access To Justice (Study Of Decision Number 1771/Pdt.G/2025/Pa.Mdn) - Fatma Aulia; Siti Nurhayati; Hasdiana Juwita Bintang (Fakultas Hukum Dehasen, 2026)
Women's agency in divorce cases demonstrates a shift in women's position from passive parties to active legal subjects in fighting for their rights through the courts. Divorce is not only understood as the end of a marriage, but also as a form of women's legal awareness in facing injustices that exist amidst a social structure that still influences patriarchy. This study focuses on the reform of women's institutions in the divorce process as well as the obstacles and supporting factors that influence it. The method used is normative-empirical law, with a normative approach to legislation and an empirical approach through interviews with judges, clerks, and plaintiffs at the Medan Religious Court. The results of the discussion indicate that, in terms of legal regulations, Law Number 1 of 1974 has provided a strong legal basis for women to face challenges such as limited legal information, social stigma, family pressure, and administrative restrictions. On the other hand, assistance, support from the Understanding Institute, the availability of legal facilities, and the gender-sensitive attitudes of judges play an important role in strengthening women's institutions to achieve real justice.